A single-nucleotide mutation of G301A in GaIAA14 confers leaf curling in Gossypium arboreum - Miao, Pengfei; Zhang, Huan; Xu, Yifan; Zhang, Ruowen; Hao, Yunfei; Song, Guoli; Liu, Ji (Frontiers in Plant Science, 2025)
Cotton is a crucial fiber and oil crop, playing a significant role in the textile and food industries. Its yield heavily relies on photosynthesis, a process that primarily occurs in the leaves. Consequently, leaf morphology stands as a vital agronomic trait in cotton breeding. However, research on the molecular mechanisms underlying cotton leaf morphogenesis remains relatively limited. Here we identified a curly leaf mutant (CU) in Gossypium arboreum by ethyl methylsulfonate (EMS) mutagenesis. The genetic analysis revealed that the curly leaf trait in this mutant is a semi-dominant characteristic controlled by a single gene. The map-based cloning of the CU locus showed a single-nucleotide mutation from G to A at the 301st positions in AUX/IAA14 protein (GaIAA14), which resulted in an amino acid substitution from valine (V) to isoleucine (I). After silencing GaIAA14 through virus-induced gene silencing (VIGS) technology in CU mutant, the leaves exhibited a flattened phenotype, indicating that GaIAA14 is a key gene regulating leaf curling in cotton. Comparative transcriptomic RNA-Seq analysis revealed significant changes in the expression levels of most auxin-related genes, suggesting that the mutation disrupts auxin signaling transduction. These findings establish a foundation for further functional studies of this gene and provide research strategies for leaf morphology improvement.